Modeling and forecasting realized portfolio diversification benefits - Vasyl Golosnoy; Benno Hildebrandt; Steffen Köhler (Journal of Risk and Financial Management, 2019)
For a financial portfolio, we suggest a realized measure of diversification benefits, which is based on intraday high-frequency returns. Our measure quantifies volatility reduction, which could be achieved by including an additional asset in the portfolio. In order to make our approach feasible for investors, we also provide time series modeling of both the realized diversification measure and realized portfolio weight. The performance of our approach is evaluated in-sample and out-of-sample. We find out that our approach is helpful for the purpose of portfolio variance minimization.
Keywords: 330; diversification benefits; HAR models; minimum variance portfolio; realized measures